Estudo experimental da Lei de Faraday da indução eletromagnética utilizando um smartphone e um computador - Reis, Tiago de Oliveira (Universidade Federal de São Carlos, 2018)
The experiment proposal aims to demonstrate Faraday's law of electromagnetic induction using a personal computer, a smartphone and low cost materials. It is expected that students recognize from a quantitative point of view, that varying the magnetic flux through a coil, leads to the generation of an induced electromotive force (emf). The detection of the emf is made using the computer's sound card and the free software Audacity. Concomitantly, measurements of the magnetic field as a function of time is made with the smartphone and the Physics Toolbox Sensor Suite (PTSS) app. The smartphone's data allows to determine the magnetic field flux's time dynamics in the coil. Such variation is associated with the emf obtained with the computer. Using a electronic spreadsheet to analyse the experimental data, students should be able to recognize the linear relationship between these two physical quantities.
Experimental study of the faraday's law of eletromagnetic induction using a smartphone and a personal computer
Keywords: Lei de Faraday; Indução eletromagnética; Tecnologias da informação e comunicação; Aquisição e análise de dados; Faraday's Law; Electromagnetic induction; Information and communication technologies; Acquisition and analysis of data; Física - Estudo e ensino; Physics - Study and teaching; CIENCIAS EXATAS E DA TERRA::FISICA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::TECNOLOGIA EDUCACIONAL